2021
DOI: 10.1038/s41598-021-91058-w
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to climate change of a microendemic lizard species from the central Andes

Abstract: Given the rapid loss of biodiversity as consequence of climate change, greater knowledge of ecophysiological and natural history traits are crucial to determine which environmental factors induce stress and drive the decline of threatened species. Liolaemus montanezi (Liolaemidae), a xeric-adapted lizard occurring only in a small geographic range in west-central Argentina, constitutes an excellent model for studies on the threats of climate change on such microendemic species. We describe field data on activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Studies on the thermal adaptation in lizards have also concluded that widely distributed species are more plastic than narrowly distributed species [84,85]. The vulnerability shown by micro-endemic species in response to climate change has been mentioned in several articles [86][87][88]. During the process of species adaptation to climate change, the mechanisms are specific, such as altering organ size and mitochondrial, proteomic, and metabolomic regulation [84].…”
Section: Differential Gene Expression Of Different Lizards In Regions...mentioning
confidence: 99%
“…Studies on the thermal adaptation in lizards have also concluded that widely distributed species are more plastic than narrowly distributed species [84,85]. The vulnerability shown by micro-endemic species in response to climate change has been mentioned in several articles [86][87][88]. During the process of species adaptation to climate change, the mechanisms are specific, such as altering organ size and mitochondrial, proteomic, and metabolomic regulation [84].…”
Section: Differential Gene Expression Of Different Lizards In Regions...mentioning
confidence: 99%
“…We started testing the righting response of the lizard when the terrarium temperature reached 8°C. Righting response was tested every 15 seconds until the lizard could not right itself Biology Open • Accepted manuscript when flipped on its back (Labra & Bozinovic, 2002;Laspiur et al, 2021). The terrarium temperatures were reduced to as low as 2°C.…”
Section: Critical Thermal Maxima (Ct Max ) and Minima (Ct Min )mentioning
confidence: 99%
“…It has been observed that a thermally stressed state makes lizards initiate a shelter-seeking behaviour [ 8 ]. Plasticity in behavioural thermoregulation, particularly shifts in microhabitat use like retreating into refuges, is an effective way to maintain their body temperature within their preferred range [ 6 , 20 , 21 ]. However, according to the “missed opportunities” hypothesis [ 22 ], when thermal quality of the environment (i.e the difference between the mean hourly operative temperature, T e , in the habitat and the set-point range of the species) is poor due to high temperatures, individuals need to spend more time shuttling between sun and refuges [ 8 , 23 ].…”
Section: Introductionmentioning
confidence: 99%